Depression in Multiple Sclerosis: Clinical Case Review and Grand Rounds - Harkishan Mamtani; Kshiteeja Jain; Sundarnag Ganjekar; M. Netravathi; Geetha Desai (Journal of Psychiatry Spectrum, 2023)
Among the numerous neuropsychiatric manifestations of multiple sclerosis (MS), depression is one of the most common psychiatric comorbidities. Depression has been associated with poor quality of life, aggravation of symptoms of MS, and poor adherence to treatment in MS. Diagnosing and managing depression in MS can be challenging. Psychiatrists, neurologists, and other allied professionals need to collaborate to manage depression effectively. There is a need for greater awareness and vigilance for depression in this vulnerable population. We present a case of MS with recurrent depressive disorder and subsequently discuss the literature relating to depression in MS.